Broadband access wireline and wireless - alternatives for internet services - Gorshe, Steve; Raghavan, Arvind R.; Starr, Thomas; Galli, Stefano (John Wiley & Sons Ltd, 2014)
Written by experts in the field, this book provides an overview of all forms of broadband subscriber access networks and technology, including fiber optics, DSL for phone lines, DOCSIS for coax, power line carrier, and wireless. Each technology is described in depth, with a discussion of key concepts, historical development, and industry standards